2019
DOI: 10.7589/2017-12-304
|View full text |Cite
|
Sign up to set email alerts
|

Health Assessment of Free-Ranging Chelonians in an Urban Section of the Bronx River, New York, Usa

Abstract: The Bronx River in Bronx, New York spans an area of significant human development and has been subject to historic and ongoing industrial contamination. We evaluated the health of free-ranging native common snapping turtles ( Chelydra serpentina) and nonnative invasive red-eared sliders ( Trachemys scripta) in a segment of the Bronx River between May and July 2012. In 18 snapping turtles and nine sliders, complete physical examinations were performed, ectoparasites collected, and blood was analyzed for contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Glyptemys herpesvirus 1 and glyptemys herpesvirus 2 were both detected in asymptomatic bog and wood turtles (Glyptemys insculpta) (26). Trachemys herpesvirus 1 has been detected in asymptomatic free ranging red-eared sliders (Trachemys scripta elegans) in the United States (27). Emydoidea herpesvirus 1 was detected in free ranging Blanding's turtles (Emydoidea blandingii) in the United States (28), while Emydoidea herpesvirus 2 was detected in a squamous cell carcinoma in the oral cavity of a free ranging Blanding's turtle (29).…”
Section: Introductionmentioning
confidence: 99%
“…Glyptemys herpesvirus 1 and glyptemys herpesvirus 2 were both detected in asymptomatic bog and wood turtles (Glyptemys insculpta) (26). Trachemys herpesvirus 1 has been detected in asymptomatic free ranging red-eared sliders (Trachemys scripta elegans) in the United States (27). Emydoidea herpesvirus 1 was detected in free ranging Blanding's turtles (Emydoidea blandingii) in the United States (28), while Emydoidea herpesvirus 2 was detected in a squamous cell carcinoma in the oral cavity of a free ranging Blanding's turtle (29).…”
Section: Introductionmentioning
confidence: 99%
“…(Adamovicz, unpublished data) and herpesviral antibody presence (Chaffin et al, 2008) have also been identified in wild turtles. While ranavirus (Carstairs et al, 2020;McKenzie et al, 2019), herpesvirus (Aplasca et al, 2019), and Mycoplasma sp. (Aplasca et al, 2019), have been detected in common snapping turtles, clinical disease appears uncommon in this species (Aplasca et al, 2019;Carstairs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While ranavirus (Carstairs et al, 2020;McKenzie et al, 2019), herpesvirus (Aplasca et al, 2019), and Mycoplasma sp. (Aplasca et al, 2019), have been detected in common snapping turtles, clinical disease appears uncommon in this species (Aplasca et al, 2019;Carstairs et al, 2020). Eastern box turtles and alligator snapping turtles utilize the lectin pathway of complement activation, while ornate box turtles and common snapping turtles use the alternative pathway; potentially indicating that the alternative pathway stimulates more comprehensive protection against invading pathogens (Baker, Kessler, Darville-Bowleg, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies have largely relied on molecular methods to identify potential genetic and environmental risk factors associated with reptilian HVs ( 24 , 80 , 138 , 167 169 ). Species-specific PCR-based assays targeting specific gene segments of reptilian HVs have been developed and validated ( 78 , 170 ).…”
Section: Diagnosismentioning
confidence: 99%
“…Generally, HVs replicate within host cell nuclei and are able to remain latent in their natural hosts ( 17 , 23 ). So far, reptilian HVs that have been identified and characterised all belong to the subfamily Alphaherpesvirinae ( 17 , 24 26 ).…”
Section: Introductionmentioning
confidence: 99%